Plant-Derived Molluscicides: Thymus vulgaris and Artemisia judaica Extracts Control the white garden snail, Thebapisana - Masouda Elzaroug; Salah Hasan; Fariha AlHaddad (AlQalam Journal of Medical and Applied Sciences, 2026)
The white garden snail Theba pisana, is a significant agricultural pest, and there is growing interest in developing natural molluscicides as alternatives to synthetic chemicals. This study evaluated the efficacy of haxsan and aqueous extracts of Thymus vulgaris and Artemisia judaica against Theba pisana using the leaf-dipping technique. Mortality was assessed after 24, 48, and 72 hours of exposure. Results demonstrated that mortality was significantly influenced by the plant species, extract type, concentration, and exposure time. haxsan extracts consistently outperformed their aqueous counterparts. The haxsan extract of T. vulgaris was the most potent, causing 93.3% mortality at a 15% concentration after 72 hours, compared to only 33.3% for its aqueous extract. Probing the data further, probit analysis confirmed the superior toxicity of haxsan extracts, with the haxsan extract of T. vulgaris having the lowest LC50 value (6.37 %), followed by the haxsan extract of A. judaica (LC50 = 8.69 %). All treated groups exhibited significantly higher mortality (p<0.001) than the control group (0%). This study conclusively shows that haxsan extracts of T. vulgaris and A. judaica possess strong, time and concentration-dependent molluscicidal activity against Theba pisana, highlighting their potential as a source for molluscicide development and integration into pest management tactics.